Biodiversity patterns in interstitial marine microturbellaria: a case study within the genus Parotoplana (Platyhelminthes: Rhabditophora) with the description of four new species. (7th January 2014) - Casu, Marco; Scarpa, Fabio; Delogu, Valentina; Cossu, Piero; Lai, Tiziana; Sanna, Daria; Curini‐Galletti, Marco
Abstract Four new species of Otoplanidae (Platyhelminthes: Rhabditophora: Proseriata) with ranges restricted to the central Mediterranean are described. These species are characterized by the presence of a tubular copulatory stylet and by a bursa lacking an open connection to the atrium. Both characters are novel for the family Otoplanidae. The four species differ mainly in details of the morphology of the sclerotized structures of the copulatory organ. Generic attribution of the new species has been problematic. Morphological characters shared with either Parotoplanina or Parotoplanella were detected. Molecular data (based on 18S rRNA and 28S D1‐D6 rRNA genes) evidenced that the new species constitute a monophyletic group falling within species of Parotoplana, with a sister/taxon relationship with Parotoplana spathifera. The genus Parotoplana, however, appears to be paraphyletic, as Parotoplanella progermaria nests within Parotoplana species. The inadequate molecular sampling, combined with the lack of sequences from the type species of both Parotoplana and Parotoplanina, suggested a cautionary taxonomic approach, and the new species are therefore attributed to the earliest generic taxon available, Parotoplana.